Potential mechanism of hepatic lipid accumulation during a long-term rest phase restricted feeding in mice. (3rd August 2022) - Tsurudome, Yuya; Akamine, Takahiro; Horiguchi, Michiko; Wada, Yukiyo; Fujimura, Akio; Ushijima, Kentaro
ABSTRACT: Eating during a rest phase disrupts the biological clock system and leads to obesity and metabolic diseases. Although a rest phase restricted feeding (RF) is reported to enhance hepatic lipid accumulation, the mechanism(s) of the phenomenon is still unknown. This study evaluated the potential involvement of the CD36-related transport of lipids into the liver in mice with the RF procedure. This study showed that hepatic lipid accumulation was more significant in the RF group compared with mice under an active phase restricted feeding (AF). The RF procedure also elevated the expression of CD36 mRNA and its protein on the cellular membrane throughout the day. The transcription factor profiling array revealed that the RF activated the proliferator-activated receptor-γ (PPARγ), one of the CD36 transcript enhancers. In the liver of RF mice, the expression of miR-27b-3p, which is known to interfere with PPARγ gene expression, significantly decreased. These results suggest that the RF procedure inhibits the expression of miR-27b-3p in the liver and subsequently elevates PPARγ activity. Activated PPARγ might lead to CD36 upregulation, which, in turn, stimulates the transport of lipids into the liver.